Progress in gallbladder cancer with lymph node metastasis - Li, Yuhang; Song, Yinghui; Zhang, Yujing; Liu, Sulai (Frontiers in Oncology, 2022)
Gallbladder cancer (GBC) is a malignant tumor that originate from the mucosal lining of the gallbladder. It is distinctly regional and is common in certain geographic areas of developing countries. GBC has a high degree of insidiousness as well as a high propensity for metastatic spread resulting in the majority of patients are diagnosed at an advanced stage. Lymph node metastasis (LNM) is fairly common in GBC patients and is an independent risk factor for the poor prognosis. This article is focused on the lymph node pathways and metastatic directions of GBC. Furthermore, it summarizes the different lymph node groupings, disease stages and treatment. In the future, it is of great significance for developing individualized treatment and predicting prognosis for GBC patients with different lymph node conditions.